Faculty Development: A Review of the (Relatively Recent) Literature and Implications for Christian Higher Education. Issue 4 (8th August 2019) - Matthias, Laurie R.
Abstract: This article is a review of the 21st century literature on faculty development in American higher education. After briefly summarizing the history of faculty development and current trends, the majority of the article is written as advice to faculty developers synthesized into the following broad themes: (a) options for structure and offerings, (b) methods for supporting faculty, and (c) strategies for positioning oneself in a crucial role within the institution in a collaborative way. More specifically, within the methods for supporting faculty, this article identifies three prevalent themes: (a) viewing faculty as individuals, particularly around career stages; (b) facilitating integration on several fronts; and (c) utilizing collaboration as a tool for achieving development goals. Addressing the implications of the literature for Christian higher education, the article suggests that these current faculty development themes offer developers in Christian institutions unique opportunities to integrate current practice with Christian foundational purposes.